The entrepreneur and the risk management. The Carlos E. Restrepo´s Case (2019)
The trajectory of Antioquia´s businessman Carlos E. Restrepo is analyzed around his commercial and industrial activities and it is shown in many of his performances the way he responded to the risks associated with his own businesses and its environment. In order to learn from his successes and failures and to help strengthen the study of Business Administration, particularly from risk management, this article contributes to the understanding of how Antioquia´s entrepreneurs of commerce and industry, between 1900 and 1930, faced the risks to which they were exposed in their activities.